Risk and Return Analysis of Closed-End Mutual Fund in Bangladesh - Chowdhury, Tasruma Sharmeen; Habibullah, Md.; Nahar, Nurun (Journal of Accounting, Business and Finance Research, 2018)
This study attempts to conduct a five-year performance assessment by analyzing all 24 closed-end mutual funds that had been trading at Dhaka Stock Exchange from December 2011 to January 2017. While analyzing the risk-return profile, the research incorporated both market price and net asset value (NAV) of the mutual funds.NAV depends on the price of securities included in a fund's portfolio whereas, the market price is determined by demand and supply forces. Thus, the market price of a fund is not always equal to its NAV. The study uses market price as a basis for analyzing the risk-return profile of the funds for evaluating the performance of the funds in the market. With the purpose of assessing the performance of asset managers, the study uses NAV as a basis for computing Jensen's α and M squared measure. While assessing performance the study focuses on Jensen’s α and M squared measure as other measures like Sharpe and Treynor do not work with negative numerators and do not provide information on whether the mutual fund outperformed the market portfolio. Both Jensen’s α and M squared measure can independently describe whether a fund beat the market or not. A positive value of Jensen’s α and M squared measure indicates that the fund outperformed the market considering respectively β and σ as a measure of risk. SEBL1STMF, POPULAR1MF, and IFILISLMF1 were among top four funds considering both M2 and Jensen’s alpha measures based on both market price and NAV. The M2 measure, a coefficient of variation, Sharpe ratio, and Treynor ranked SEBL1STMF as the best performer in the market. This fund also topped while assessing performance by M2 measure on the basis of NAV. On the basis of market price and NAV, 21 funds and 22 funds could produce positive M2 respectively. In the year 2012, 2013 and 2014 mutual funds provided negative annualized return on an average (On the basis of market price). The average annualized return rebounded on 2015 and further increased on 2016. All mutual funds provided a positive return in 2016. A different picture was found while calculating annualized return on the basis of NAV, asset managers could generate positive annualized returns on an average in 2013, 2014, 2015 and 2016.